PEO-based composite solid electrolyte membrane and preparation method thereof, solid-state battery
By introducing low-entropy multi-element doped lithiate Li8Ge1/3Pb1/3Sn1/3O6 into PEO-based solid electrolytes, the problem of insufficient conductivity and mechanical properties of PEO-based solid electrolytes is solved, higher ion conductivity and structural stability are achieved, and the electrochemical performance of lithium-ion batteries is improved.
Patent Information
- Application Number
- CN202510012115.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The existing PEO-based solid electrolyte has low conductivity and limited mechanical properties, making it difficult to meet the high performance needs of lithium-ion batteries.
The low-entropy multi-element doped lithiide Li8Ge1/3Pb1/3Sn1/3O6 was used to recombinate it with PEO and lithium-based electrolyte, and MOF materials were synthesized by hydrothermal method and lithiated sintering to prepare porous low-entropy multi-element doped lithiide, which improved the mechanical strength and ionic conductivity of the electrolyte.
The ion conductivity and structural stability of the PEO-based composite solid electrolyte membrane are improved, the reversible deintercalation ability of lithium ions is enhanced, and the electrochemical performance and cyclic reversibility are improved.
Smart Images

Figure CN119419345B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid electrolytes, and in particular relates to a PEO-based composite solid electrolyte membrane and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have a huge impact on people's daily lives and social and economic development. Their applications have covered many fields such as portable devices, automobiles, energy storage power stations, etc. At present, lithium-ion batteries mainly use conventional liquid electrolytes, which contain flammable organic matter, which seriously affects the safety of the battery. This is also a drawback that needs to be improved urgently.
[0003] Solid electrolytes have been extensively studied by researchers due to their structural stability, safety, and fast ion conductivity. Among them, organic polymer electrolytes can be used in various forms of batteries due to their organic chain structure. Among organic polymer electrolytes, polyethylene oxide (PEO) is currently recognized as the most suitable matrix for preparing all-solid electrolytes. Since PEO has a strong coordination ability, it can be complexed with lithium-based electrolytes. However, PEO-based solid electrolytes generally have low conductivity and limited mechanical properties, so they need to be composite modified. Summary of the invention
[0004] In response to the above technical problems, the present application provides a PEO-based composite solid electrolyte membrane and a preparation method thereof, and a solid-state battery.
[0005] To achieve the above objectives, this application proposes the following technical solutions:
[0006] In a first aspect, a PEO-based composite solid electrolyte membrane is provided, comprising a low-entropy multi-element doped lithium compound, PEO and a lithium-based electrolyte, wherein the chemical formula of the low-entropy multi-element doped lithium compound is Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6.
[0007] Furthermore, the ratio of the mass of the low-entropy multi-element doped lithium compound to the total mass of PEO and the lithium-based electrolyte is 5-15:100.
[0008] Furthermore, the molar ratio of PEO to lithium-based electrolyte is 15-20:1.
[0009] Furthermore, the lithium-based electrolyte is at least one of LiTFSI, LiFSI, and LiBF4.
[0010] Furthermore, the low-entropy multi-element doped lithium compound is a porous material.
[0011] In a second aspect, a method for preparing a PEO-based composite solid electrolyte membrane is provided, comprising:
[0012] Preparation of low entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6;
[0013] The low entropy multi-element doped lithium compound is uniformly mixed with PEO and a lithium-based electrolyte, and then an organic solvent is added to grind the mixture to obtain a slurry, which is then coated and vacuum dried to obtain a PEO-based composite solid electrolyte membrane.
[0014] Furthermore, the preparation of low entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6 includes:
[0015] Prepare Ge-MOF material, prepare PbSn-MOF material, mix Ge-MOF and PbSn-MOF according to the molar ratio of Ge to Pb and Sn of 1:1:1 to obtain a precursor, mix the precursor with a lithium source uniformly, and then sinter to obtain a porous low-entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6.
[0016] Furthermore, the preparation of the Ge-MOF material includes: dispersing a germanium source in a mixed solvent of water and an alkaline organic solvent, adding an amine organic ligand, performing a hydrothermal reaction, and subjecting the obtained product to solid-liquid separation to obtain the Ge-MOF material.
[0017] Furthermore, the preparation of the PbSn-MOF material includes: dispersing a lead source and a tin source in water at a molar ratio of Pb to Sn of 1:1, adding a carboxylic acid organic ligand, performing a hydrothermal reaction, and subjecting the obtained product to solid-liquid separation to obtain the PbSn-MOF material.
[0018] Furthermore, the germanium source is germanium dioxide.
[0019] Furthermore, the alkaline organic solvent is one or both of pyridine and dimethylformamide.
[0020] Furthermore, the amine organic ligand is one or more of ethylenediamine, triethylamine and 2-methylpyrazine.
[0021] Furthermore, the molar ratio of the germanium source to the amine organic ligand is 1:4-10.
[0022] Furthermore, the molar ratio of water to alkaline organic solvent is 0.2-0.5:0.8-2.
[0023] Furthermore, the molar ratio of the germanium source to the alkaline organic solvent is 1:0.8-2.
[0024] Furthermore, the carboxylic acid organic ligand is one or more of terephthalic acid and its derivative polyacids, trimesic acid and its derivative polyacids, phthalic acid and its derivative polyacids.
[0025] Furthermore, the lead source is lead nitrate and / or lead acetate.
[0026] Furthermore, the tin source is tin sulfate.
[0027] Furthermore, the molar ratio of lead in the lead source to tin and carboxylic acid organic ligand in the tin source is 1:1:5-10.
[0028] Furthermore, the molar ratio of the lead source to water is 1:50-80.
[0029] Furthermore, when synthesizing the Ge-MOF, the temperature of the hydrothermal reaction is 160-220° C., and the time of the hydrothermal reaction is 40-100 h.
[0030] Furthermore, when synthesizing the PbSn-MOF, the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 20-60 h.
[0031] Furthermore, the sintering temperature is 800-1000° C., and the sintering time is 10-30 hours.
[0032] Furthermore, the lithium source is one or more of lithium oxide, lithium carbonate and lithium hydroxide.
[0033] Furthermore, the ratio of the total metal molar amount in the precursor material to the lithium molar amount in the lithium source is 3:24.04~24.08.
[0034] Furthermore, the organic solvent is one of acetonitrile, tetrahydrofuran and N,N-dimethylformamide.
[0035] In a third aspect, a solid-state battery is provided, comprising the aforementioned PEO-based composite solid-state electrolyte membrane or a PEO-based composite solid-state electrolyte membrane prepared by the aforementioned preparation method.
[0036] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects:
[0037] (1) Provide PEO-based composite solid electrolyte membranes, including Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3O6, PEO and lithium-based electrolytes, the PEO-based composite solid electrolyte membrane has excellent ion conductivity and structural stability, and has excellent cycle reversibility and electrochemical performance when used in solid-state batteries.
[0038] (2) In the PEO-based composite solid electrolyte membrane provided, Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6 has higher porosity and higher specific surface area, which enables PEO-based electrolytes to be perfectly compounded with it, effectively improving the mechanical strength of PEO-based solid electrolytes. In addition, it can provide more active sites for the reversible insertion and extraction of lithium ions, thereby improving the reaction kinetics and conductivity.
[0039] (3) The low-entropy multi-element doped MOF material is synthesized by hydrothermal method, and then further lithiated and sintered to prepare a porous low-entropy multi-element doped lithium compound, which is compounded with the main component of the solid electrolyte PEO and the lithium-based electrolyte to finally form a porous low-entropy multi-element doped modified PEO-based composite solid electrolyte membrane. The porous low-entropy multi-element doped lithium compound has a high porosity and a high specific surface area, which enables the PEO-based electrolyte to be perfectly compounded with it, effectively improving the mechanical strength of the PEO-based solid electrolyte. In addition, it can also provide more active sites for the reversible insertion and extraction of lithium ions, thereby improving the reaction kinetics and conductivity. The low-entropy multi-element doped lithium compound itself contains a high content of lithium source, which can provide the necessary lithium source sites for the lithium-based electrolyte, ensuring the cyclic reversibility and ion conductivity of the solid electrolyte.
[0040] (4) The preparation process of the present invention is simple, the process is short, the raw materials are easily available, no toxic or harmful substances are produced during the preparation process, and it is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 Li8Ge obtained in step (2) of Example 1 1 / 3 Pb 1 / 3 Sn 1 / 3 SEM image of O6.
[0043] Figure 2 Li8Ge obtained in Example 1 1 / 3 Pb 1 / 3 Sn 1 / 3SEM image of O6-modified PEO-based composite solid electrolyte membrane.
[0044] Figure 3 The cycle performance diagram of button cells assembled with the modified PEO-based composite solid electrolyte membrane prepared in Examples 1 to 3 and Comparative Examples 1 to 3 as the solid electrolyte component. DETAILED DESCRIPTION
[0045] Some embodiments of the present invention provide a PEO-based composite solid electrolyte membrane, comprising a low-entropy multi-element doped lithium compound, PEO and a lithium-based electrolyte, wherein the chemical formula of the low-entropy multi-element doped lithium compound is Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6.
[0046] In some preferred embodiments, the ratio of the mass of the low-entropy multi-element doped lithium compound to the total mass of PEO and the lithium-based electrolyte is 5 to 15:100, for example, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, etc.
[0047] In some preferred embodiments, the molar ratio of PEO to lithium-based electrolyte is 15-20:1, for example, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, etc.
[0048] In some preferred embodiments, the lithium-based electrolyte is at least one of LiTFSI, LiFSI, and LiBF4.
[0049] In some preferred embodiments, the low-entropy multi-element doped lithium compound is a porous material.
[0050] Some embodiments of the present invention provide a method for preparing a PEO-based composite solid electrolyte membrane, comprising:
[0051] Preparation of low entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6;
[0052] The low entropy multi-element doped lithium compound is uniformly mixed with PEO and a lithium-based electrolyte, and then an organic solvent is added to grind the mixture to obtain a slurry, which is then coated and dried to obtain a PEO-based composite solid electrolyte membrane.
[0053] In some preferred embodiments, the preparation of low entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6 includes:
[0054] Prepare Ge-MOF material and PbSn-MOF material, mix Ge-MOF and PbSn-MOF according to the molar ratio of Ge to Pb and Sn of 1:1:1 to obtain a precursor, evenly mix the precursor with a lithium source, and then sinter at a high temperature to obtain a porous low-entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6.
[0055] In some preferred embodiments, the preparation of Ge-MOF material includes: dispersing a germanium source in a mixed solvent of water and an alkaline organic solvent, adding an amine organic ligand, performing a hydrothermal reaction, and subjecting the obtained product to solid-liquid separation to obtain the Ge-MOF material.
[0056] In some embodiments, the germanium source is germanium dioxide.
[0057] In some embodiments, the alkaline organic solvent is one or both of pyridine and dimethylformamide.
[0058] In some embodiments, the amine organic ligand is one or more of ethylenediamine, triethylamine, and 2-methylpyrazine.
[0059] In some preferred embodiments, the molar ratio of the germanium source to the amine organic ligand is 1:4-10, for example, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.
[0060] In some preferred embodiments, the molar ratio of water to the alkaline organic solvent is 0.2-0.5:0.8-2, for example, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.
[0061] In some preferred embodiments, the molar ratio of the germanium source to the alkaline organic solvent is 1:0.8-2, for example, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, etc.
[0062] In some preferred embodiments, when synthesizing the Ge-MOF, the temperature of the hydrothermal reaction is 160-220°C, for example, 160°C, 180°C, 200°C, 220°C, etc., and the time of the hydrothermal reaction is 40-100h, for example, 40h, 60h, 80h, 100h, etc.
[0063] In some preferred embodiments, the preparation of the PbSn-MOF material includes: dispersing a lead source and a tin source in water at a molar ratio of Pb to Sn of 1:1, adding a carboxylic acid organic ligand, conducting a hydrothermal reaction, and subjecting the obtained product to solid-liquid separation to obtain the PbSn-MOF material.
[0064] In some preferred embodiments, the carboxylic acid organic ligand is one or more of terephthalic acid and its derivative polyacids, trimesic acid and its derivative polyacids, phthalic acid and its derivative polyacids;
[0065] In some embodiments, the lead source is a soluble lead source, such as lead nitrate and / or lead acetate.
[0066] In some embodiments, the tin source is a soluble tin source, such as tin sulfate.
[0067] In some preferred embodiments, the molar ratio of lead in the lead source to tin and carboxylic acid organic ligands in the tin source is 1:1:5-10, for example, 1:1:5, 1:1:6, 1:1:7, 1:1:8, 1:1:9, 1:1:10, etc.
[0068] In some preferred embodiments, the molar ratio of the lead source to water is 1:50-80, for example, 1:50, 1:60, 1:70, 1:80, etc.
[0069] In some preferred embodiments, when synthesizing the PbSn-MOF, the temperature of the hydrothermal reaction is 160-200°C, for example, 160°C, 170°C, 180°C, 190°C, 200°C, etc., and the time of the hydrothermal reaction is 20-60h, for example, 20h, 30h, 40h, 50h, 60h, etc.
[0070] In some preferred embodiments, the high temperature sintering temperature is 800-1000°C, for example, 800°C, 850°C, 900°C, 950°C, 1000°C, etc., and the high temperature sintering time is 10-30h, for example, 10h, 15h, 20h, 25h, 30h, etc.
[0071] The lithium source may be a conventional lithium source in the art, such as one or more of lithium oxide, lithium carbonate, and lithium hydroxide.
[0072] In some preferred embodiments, the ratio of the total metal molar amount in the precursor material to the lithium molar amount in the lithium source is 3:24.04-24.08.
[0073] It is worth noting that when an organic solvent is added for grinding to prepare a slurry, the organic solvent can be a conventional solvent in the art, such as acetonitrile, tetrahydrofuran, or N,N-dimethylformamide. The amount of the organic solvent can be determined conventionally.
[0074] It is worth noting that when the film is prepared by re-coating, the subsequent drying can be conventional vacuum drying; the parameters of the vacuum drying can also adopt conventional parameters, such as a drying temperature of 70 to 90° C. and a drying time of 6 to 12 hours.
[0075] Some embodiments provide a solid-state battery, comprising the aforementioned PEO-based composite solid electrolyte membrane or a PEO-based composite solid electrolyte membrane prepared by the aforementioned preparation method.
[0076] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0077] Example 1
[0078] (1) Disperse 0.1 mol GeO2 in 0.54 ml deionized water and 0.12 mol pyridine, add 0.8 mol triethylamine, and carry out hydrothermal reaction at 200 °C for 60 h to form Ge-MOF; then disperse 0.1 mol lead nitrate and 0.1 mol tin sulfate evenly in 100 ml deionized water, add 0.8 mol terephthalic acid, and carry out hydrothermal reaction at 180 °C for 40 h to form PbSn-MOF. After mixing the prepared Ge-MOF and PbSn-MOF, a low-entropy multi-element doped lithium precursor material is obtained.
[0079] (2) After the precursor material in step (1) is uniformly mixed with 1.203 mol of lithium oxide, it is placed in a muffle furnace for high-temperature sintering at 900°C for 12 hours to finally prepare a low-entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6, its SEM picture is as follows Figure 1 As shown, from Figure 1 It can be seen that the obtained low entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6 is a porous material.
[0080] (3) Take 2g of Li8Ge prepared in step (2) 1 / 3 Pb 1 / 3 Sn 1 / 3O6 was mixed with 20g of solid electrolyte main components PEO and LiTFSI (the total mass of PEO and LiTFSI was 20g) in a solid phase, wherein the molar ratio of PEO to LiTFSI was 18:1. Acetonitrile was then added dropwise, and the mixture was continuously ground to uniformly disperse into a slurry, which was then uniformly coated on a polytetrafluoroethylene plate and dried at 80°C in vacuum for 8h to obtain Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6 modified PEO based composite solid electrolyte membrane, its SEM image is as follows Figure 2 As shown, from Figure 2 It can be seen that the membrane surface is flat, which is conducive to the effective contact between the electrolyte membrane and the material.
[0081] Comparative Example 1
[0082] (1) Disperse 0.1 mol GeO2 in 0.54 ml deionized water and 0.12 mol pyridine, add 0.8 mol triethylamine, and perform hydrothermal reaction at 200 °C for 60 h to form Ge-MOF.
[0083] (2) After the Ge-MOF precursor material in step (1) is uniformly mixed with 0.4 mol of lithium oxide, it is placed in a muffle furnace for high-temperature sintering at 900°C for 12 hours, and finally a porous low-entropy multi-element doped lithium compound Li8GeO6 is prepared.
[0084] (3) Take 1g of Li8GeO6 prepared in step (2) and 20g of the main components of the solid electrolyte PEO and LiTFSI for solid phase uniform mixing, wherein the molar ratio of PEO to LiTFSI is 18:1. Then, acetonitrile is added dropwise, and the mixture is continuously ground to be uniformly dispersed into a slurry, which is uniformly coated on a polytetrafluoroethylene plate, and then vacuum dried at 80°C for 8h to obtain a Li8GeO6-modified PEO-based composite solid electrolyte membrane.
[0085] Comparative Example 2
[0086] (1) 0.1 mol of lead nitrate and 0.1 mol of tin sulfate were evenly dispersed in 100 ml of deionized water, 0.8 mol of terephthalic acid was added, and a hydrothermal reaction was carried out at 180 °C for 40 h to form PbSn-MOF.
[0087] (2) After the PbSn-MOF precursor material in step (1) is uniformly mixed with 0.8 mol of lithium oxide, it is placed in a muffle furnace for high-temperature sintering at 900°C for 12 hours to finally prepare a porous low-entropy multi-element doped lithium compound Li8Pb 1 / 2 Sn 1 / 2O6.
[0088] (3) Take 1g of Li8Pb prepared in step (2)1 / 2 Sn 1 / 2 O6 was mixed with 20g of solid electrolyte main components PEO and LiTFSI in a solid phase, wherein the molar ratio of PEO to LiTFSI was 18:1. Acetonitrile was then added dropwise, and the mixture was continuously ground to be uniformly dispersed into a slurry, which was then uniformly coated on a polytetrafluoroethylene plate and dried at 80°C in vacuum for 8h to obtain Li8Pb 1 / 2 Sn 1 / 2 O6 modified PEO-based composite solid electrolyte membrane.
[0089] Comparative Example 3
[0090] PEO and LiTFSI were uniformly mixed in the solid phase at a molar ratio of 18:1, and then acetonitrile was dropped into it and continuously ground to make it uniformly dispersed into a slurry. The slurry was evenly coated on a polytetrafluoroethylene plate and vacuum dried at 80°C for 8h to obtain a PEO-based electrolyte membrane.
[0091] Example 2
[0092] (1) Disperse 0.1 mol GeO2 in 0.9 ml deionized water and 0.2 mol dimethylformamide, add 1 mol 2-methylpyrazine, and carry out hydrothermal reaction at 220 °C for 40 h to form Ge-MOF; then disperse 0.1 mol lead acetate and 0.1 mol tin sulfate evenly in 144 ml deionized water, add 1 mol trimesic acid, and carry out hydrothermal reaction at 200 °C for 20 h to form PbSn-MOF. After mixing the prepared Ge-MOF and PbSn-MOF, a low-entropy multi-element doped lithium precursor material is obtained.
[0093] (2) After the precursor material in step (1) is uniformly mixed with 1.204 mol of lithium carbonate, it is placed in a muffle furnace for high-temperature sintering at 1000°C for 10 h to finally prepare a porous low-entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6.
[0094] (3) Take 3g of Li8Ge prepared in step (2) 1 / 3 Pb 1 / 3 Sn 1 / 3 O6 was mixed with 20g of solid electrolyte main components PEO and LiFSI (the total mass of PEO and LiFSI was 20g) in a solid phase, wherein the molar ratio of PEO to LiFSI was 20:1. Then tetrahydrofuran was added dropwise, and the mixture was continuously ground to be uniformly dispersed into a slurry, which was evenly coated on a polytetrafluoroethylene plate and dried at 90°C in vacuum for 6h to obtain Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3O6 modified PEO-based composite solid electrolyte membrane.
[0095] Example 3
[0096] (1) Disperse 0.1 mol GeO2 in 0.36 ml deionized water and 0.08 mol dimethylformamide, add 0.4 mol 2-methylpyrazine, and carry out hydrothermal reaction at 160 ° C for 100 h to form Ge-MOF; then disperse 0.1 mol lead acetate and 0.1 mol tin sulfate evenly in 90 ml deionized water, add 0.5 mol trimesic acid, and carry out hydrothermal reaction at 160 ° C for 60 h to form PbSn-MOF. After mixing the prepared Ge-MOF and PbSn-MOF, a low-entropy multi-element doped lithium precursor material is obtained.
[0097] (2) After the precursor material in step (1) is uniformly mixed with 2.404 mol of lithium hydroxide, it is placed in a muffle furnace for high-temperature sintering at 1000°C for 10 h to finally prepare a porous low-entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3O6.
[0098] (3) Take 1g of Li8Ge prepared in step (2) 1 / 3 Pb 1 / 3 Sn 1 / 3 O6 was mixed with 20g of solid electrolyte main components PEO and LiBF4 (the total mass of PEO and LiBF4 was 20g) in a solid phase, wherein the molar ratio of PEO to LiBF4 was 15:1. Then N,N-dimethylformamide was added dropwise, and the mixture was continuously ground to be uniformly dispersed into a slurry, which was then evenly coated on a polytetrafluoroethylene plate and dried at 90°C in vacuum for 6h to obtain Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6 modified PEO-based composite solid electrolyte membrane.
[0099] The battery assembly is completed by:
[0100] The modified PEO-based composite solid electrolyte membrane obtained in Examples 1 to 3 and Comparative Examples 1 to 3 was assembled into a button cell as a solid electrolyte component, with LiFePO4 as the positive electrode and a lithium sheet as the negative electrode. The cells were placed in a glove box filled with argon atmosphere with a water content and an oxygen content both lower than 0.1 ppm for 4 hours to reduce the moisture adsorbed by the electrode during the transfer process, and then assembled into a CR2032 solid-state button cell in the glove box.
[0101] After the battery is assembled and aged for 12 hours, it is tested for charge and discharge at different potentials. The battery is activated for 3 cycles at a voltage of 2.5-4.2V and a current density of 0.1C, and then cycled for 100 cycles at a current density of 1C. The cycle performance is shown in the figure below. Figure 3 shown.
[0102] from Figure 3 It can be seen that compared with the unmodified PEO-based electrolyte membrane and the Li8GeO6 and Li8Pb 1 / 2 Sn 1 / 2 O6 modified PEO based composite solid electrolyte membrane, using Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 The battery assembled with O6-modified PEO-based composite solid electrolyte membrane has improved initial capacity and significantly improved cycle performance. Figure 3 It can also be seen that the Li8Ge prepared in each embodiment 1 / 3 Pb 1 / 3 Sn 1 / 3 The batteries assembled with O6-modified PEO-based composite solid electrolyte membrane have good electrochemical properties.
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A PEO-based composite solid electrolyte membrane, characterized in that: It includes a low entropy multi-element doped lithium compound, PEO and a lithium-based electrolyte, wherein the chemical formula of the low entropy multi-element doped lithium compound is Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6; the ratio of the mass of the low-entropy multi-element doped lithium compound to the total mass of PEO and the lithium-based electrolyte is 5~15:100; the molar ratio of PEO and the lithium-based electrolyte is 15~20:1; the low-entropy multi-element doped lithium compound is a porous material.
2. The PEO-based composite solid electrolyte membrane according to claim 1, characterized in that: The lithium-based electrolyte is at least one of LiTFSI, LiFSI, and LiBF4.
3. The method for preparing a PEO-based composite solid electrolyte membrane according to claim 1 or 2, characterized in that: include: Preparation of low entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6; The low entropy multi-element doped lithium compound is uniformly mixed with PEO and a lithium-based electrolyte, and then an organic solvent is added to grind the mixture to obtain a slurry, which is then coated and vacuum dried to obtain a PEO-based composite solid electrolyte membrane.
4. The method for preparing a PEO-based composite solid electrolyte membrane according to claim 3, characterized in that: Preparation of low entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6 includes: Prepare PbSn-MOF material, mix Ge-MOF and PbSn-MOF materials according to the molar ratio of Ge to Pb and Sn of 1:1:1 to obtain a precursor, mix the precursor with a lithium source evenly, and then sinter to obtain a porous low-entropy multi-element doped lithium compound Li8Ge 1 / 3 Pb 1 / 3 Sn 1 / 3 O6.
5. The method for preparing a PEO-based composite solid electrolyte membrane according to claim 4, characterized in that: The preparation method of the Ge-MOF comprises: dispersing a germanium source in a mixed solvent of water and an alkaline organic solvent, adding an amine organic ligand, performing a hydrothermal reaction, and performing solid-liquid separation on the obtained product to obtain a Ge-MOF material; The preparation of the PbSn-MOF material comprises: dispersing a lead source and a tin source in water at a molar ratio of Pb to Sn of 1:1, adding a carboxylic acid organic ligand, performing a hydrothermal reaction, and performing solid-liquid separation on the obtained product to obtain the PbSn-MOF material.
6. The method for preparing a PEO-based composite solid electrolyte membrane according to claim 5, characterized in that: The germanium source is germanium dioxide; The alkaline organic solvent is one or two of pyridine and dimethylformamide; The amine organic ligand is one or more of ethylenediamine, triethylamine and 2-methylpyrazine; The molar ratio of the germanium source to the amine organic ligand is 1:4-10; When preparing the Ge-MOF, the molar ratio of water to alkaline organic solvent is 0.2-0.5:0.8-2; The molar ratio of the germanium source to the alkaline organic solvent is 1:0.8-2; The carboxylic acid organic ligand is one or more of terephthalic acid and its derivative polyacids, trimesic acid and its derivative polyacids, phthalic acid and its derivative polyacids; The lead source is lead nitrate and / or lead acetate; the tin source is tin sulfate; The molar ratio of lead in the lead source to tin and carboxylic acid organic ligand in the tin source is 1:1:5-10; When preparing the PbSn-MOF material, the molar ratio of the lead source to water is 1:50-80.
7. The method for preparing a PEO-based composite solid electrolyte membrane according to claim 5, characterized in that: When synthesizing the Ge-MOF, the temperature of the hydrothermal reaction is 160-220° C., and the time of the hydrothermal reaction is 40-100 h; When synthesizing the PbSn-MOF material, the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 20-60 hours.
8. The method for preparing a PEO-based composite solid electrolyte membrane according to claim 4, characterized in that: The sintering temperature is 800-1000° C., and the sintering time is 10-30 hours.
9. The method for preparing a PEO-based composite solid electrolyte membrane according to claim 4, characterized in that: The lithium source is one or more of lithium oxide, lithium carbonate and lithium hydroxide; The ratio of the total metal molar amount in the precursor to the lithium molar amount in the lithium source is 3:24.04-24.08; The organic solvent is one of acetonitrile, tetrahydrofuran and N,N-dimethylformamide.
10. A solid-state battery, characterized in that It comprises the PEO-based composite solid electrolyte membrane as described in claim 1 or 2 or a PEO-based composite solid electrolyte membrane prepared by the preparation method as described in any one of claims 3 to 9.
Citation Information
Patent Citations
Composite electrolytes
CN107710455A
Solid electrolyte
CN114614080A